2016
DOI: 10.1016/j.phrs.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D supplementation alter plasma adipokines concentrations? A systematic review and meta-analysis of randomized controlled trials

Abstract: We aimed to elucidate the role of vitamin D supplementation on adipokines through a systematic review and a meta-analysis of randomized placebo-controlled trials (RCTs). The search included PUBMED, Scopus, Web of Science and Google Scholar through July 1st, 2015. Finally we identified 9 RCTs and 484 participants. Meta-analysis of data from 7 studies did not find a significant change in plasma adiponectin concentrations following vitamin D supplementation (mean difference [MD]: 4.45%, 95%CI: -3.04, 11.93, p=0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 46 publications
2
43
1
1
Order By: Relevance
“…While it should be noted that the placebo group tended to have slightly milder baseline measures of severe obesity and metabolic dysfunction compared to the vitamin D group, these differences were not statistically significant and, thus, we hypothesize that this divergence played a negligible effect on the main findings of this study. In support of our findings obtained by WIB on cholecalciferol and placebo, previous studies showed that supplementation with vitamin D 3 at therapeutic doses did not impact total adiponectin concentrations [27], but it selectively increased HMW-A levels in obese adolescents treated for 1 year with cholecalciferol [28]. While our study and other studies failed to record associations between short-term increases of HMW-A and improvements in insulin sensitivity [20,21], long-term studies documented a significant correlation between modifications of HMW-A and insulin sensitivity [29,30,48].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While it should be noted that the placebo group tended to have slightly milder baseline measures of severe obesity and metabolic dysfunction compared to the vitamin D group, these differences were not statistically significant and, thus, we hypothesize that this divergence played a negligible effect on the main findings of this study. In support of our findings obtained by WIB on cholecalciferol and placebo, previous studies showed that supplementation with vitamin D 3 at therapeutic doses did not impact total adiponectin concentrations [27], but it selectively increased HMW-A levels in obese adolescents treated for 1 year with cholecalciferol [28]. While our study and other studies failed to record associations between short-term increases of HMW-A and improvements in insulin sensitivity [20,21], long-term studies documented a significant correlation between modifications of HMW-A and insulin sensitivity [29,30,48].…”
Section: Discussionsupporting
confidence: 89%
“…Partly contradictory results exist on the adipogenic effect of 1,25(OH) 2 Vit D [37], which was shown to inhibit adipogenesis in 3T3-L1 mouse preadipocyte cell lines [49], while promoting adipogenesis and increasing adiponectin expression in primary mouse and human subcutaneous preadipocytes [50]. Similarly, treatment with 1,25(OH) 2 Vit D in 3T3-L1 cells was found to stimulate the synthesis of adiponectin and its multimeric forms [27]. Moreover, a key regulator of folding and assembly of adiponectin, the endoplasmatic reticulum (ER) chaperon DsbA-L, was found to be upregulated by 1,25(OH) 2 Vit D, which suggests that vitamin D regulation of adiponectin may involve post-transcriptional mechanism/s [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of observational studies and randomised controlled trials has demonstrated an inverse association between leptin levels and 25(OH)D concentration in observational studies, which was not corroborated in intervention studies with high heterogeneity [56]. Another meta-analysis that aimed to elucidate the role of vitamin D supplementation on serum adipokines failed to demonstrate a significant effect of vitamin D treatment on adiponectin and leptin levels [57]. …”
Section: Osas and Vitamin D Insufficiencymentioning
confidence: 99%
“…Higher adiponectin levels are attributed to a lower risk of developing type 2 diabetes mellitus (T2DM) with a dose-response relationship [3, 4]. Glucose-lowering and insulin sensitizing effects have been observed after administration of adiponectin in mice [2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%